MiR-151a: a robust endogenous control for normalizing small extracellular vesicle cargo in human cancer - Miranda Burdiel; Julia Jiménez; Carlos Rodríguez-Antolín; Álvaro García-Guede; Olga Pernía; Ana Sastre-Perona; Rocío Rosas-Alonso; Julián Colmenarejo; Carmen Rodríguez-Jiménez; María Dolores Diestro; Virginia Martínez-Marín; Oliver Higueras; et al. (BMC, 2023)
Abstract Small extracellular vesicles (sEVs) in the blood of cancer patients contain higher amounts of tumor markers than those identified as free-circulating. miRNAs have significant biomedical relevance due to their high stability and feasible detection. However, there is no reliable endogenous control available to measure sEVs-miRNA content, impairing the acquisition of standardized consistent measurements in cancer liquid biopsy. In this study, we identified three miRNAs from a panel of nine potential normalizers that emerged from a comprehensive analysis comparing the sEV-miRNA profile of six lung and ovarian human cancer cell lines in the absence of or under different conditions. Their relevance as normalizers was tested in 26 additional human cancer cell lines from nine different tumor types undergoing chemotherapy or radiotherapy treatment. The validation cohorts were comprised of 242 prospective plasma and ascitic fluid samples from three different human tumor types. Variability and normalization properties were tested in comparison to miR-16, the most used control to normalize free-circulating miRNAs in plasma. Our results indicate that miR-151a is consistently represented in small extracellular vesicles with minimal variability compared to miR-16, providing a novel normalizer to measure small extracellular vesicle miRNA content that will benefit liquid biopsy in cancer patients.